Perlindungan Hukum Pada Konservasi Lahan Pertanian Yang Berbasis Keadilan Sosial Di Kabupaten Bolaang Mongondow - Moh. Vazri Damopolii; Fenty U. Puluhulawa; Zamroni Abdussamad (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine legal protection for agricultural land conservation in Bolaang Mongondow Regency based on social justice and to determine the implementation of Law Number 41 of 2009 concerning Sustainable Food Agricultural Land Protection regarding Agricultural Land Conservation in Bolaang Mongondow Regency. This research method uses empirical legal research methods.The results of the research that legal protection for agricultural land conservation in Bolaang Mongondow Regency based on social justice requires special attention. That farmers in the area have limited knowledge about agricultural land protection laws, which creates uncertainty in dealing with changes in land use and threats to the sustainability of agricultural land. Farmers' concerns about changes in land use illustrate the need to increase legal awareness and education among them. This increase in knowledge not only involves rights and obligations related to agricultural land, but also understanding the importance of active participation in decision making regarding agricultural land. Implementation of Law Number 41 of 2009 concerning Protection of Sustainable Food Agricultural Land, there are findings that although this law sets clear requirements for the transfer of agricultural land, practices in the field still indicate a threat to the sustainability of agricultural land. The need for active involvement of local governments in preventing practices that are detrimental to farmers and threaten the sustainability of agricultural land needs to be increased. Protection of farmers' rights, agricultural sustainability and social justice must be the main focus in ensuring that the implementation of the law achieves the desired objectives. Evaluation of cooperation between factories, local governments and farmers is also important to ensure balance and fairness in the distribution of economic benefits and legal protection.